J.M. Blázquez Martínez. El nacimiento del cristianismo, Madrid, Ed. Síntesis, 1990. Historia Universal Antigua. 16, 192 pp. - López Monteagudo, Guadalupe (Gerión. Revista de Historia Antigua, 1991)
Sin resumen